Disputing Irrational Belief in Adolescent Using Cognitive Simulation: A Case Study - Adnan Arafani; Ciptro Handrianto; Yeni Karneli; Ahmet Serhat Uçar (Universitas Negeri Padang, 2021)
The adolescent problems discussed in individual counselling sessions vary widely. The approach the counsellor uses has an effect on the way the problem is solved and the follow-up determines the recurrence of the same problem. The use of Rational Emotive Behavior Therapy focuses on aspects of irrational thinking as the root of individual problems. This article examines the case of a teenager and then determines the existing irrational thought patterns. This study uses a qualitative case study method by analyzing the counselling process. This study concluded that adolescents with emotional maturity tend to be potentially irrational by